2012
DOI: 10.1002/app.36493
|View full text |Cite
|
Sign up to set email alerts
|

Emodin voltammetric sensor based on molecularly imprinted polymer membrane‐modified electrode using a multiple hydrogen bonds strategy

Abstract: Similar to those in complementary nucleotides' base pairs, we present a novel molecularly imprinted electrochemical sensor for emodin, constructed using a multiple hydrogen bonds strategy. We obtained the sensor by in situ photopolymerization, using allobarbital as a new functional monomer. We optimized the conditions of membrane imprinting and the composition of adsorption solvent. This artificial receptor exhibits high selectivity for the template in comparison with closely related analogs, aloin A and simet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this work, Desorption time was also optimized at the same time. In brief, different time intervals (i.e., 5,10,15,20,25,30,40 and 60 min) were evaluated, respectively. The results showed that the desorptioning amounts of the template molecular did not increased along with the time prolonged after 20 min.…”
Section: Extraction and Desorption Timementioning
confidence: 99%
See 1 more Smart Citation
“…In this work, Desorption time was also optimized at the same time. In brief, different time intervals (i.e., 5,10,15,20,25,30,40 and 60 min) were evaluated, respectively. The results showed that the desorptioning amounts of the template molecular did not increased along with the time prolonged after 20 min.…”
Section: Extraction and Desorption Timementioning
confidence: 99%
“…Up to now, a great deal of extraction or methods [1][2][3][4] have been developed to realize the extraction of natural products from TCM, but the low abundance, complex composition, thermosensitive and easily hydrolyze of the natural products increased the difficult for their extraction. At the same time, most of these methods are always high-cost and time-consuming in the preparation process [5], and majority of these methods could not obtain selective recognition during the extraction. Thus a material, which has high selectivity for target analytes and can be prepared without much labor was expected.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [ 296 ] develop a voltammetric sensor based on MIM-modified electrode by creating a membrane layer (via photopolymerization) on the surface of a glassy carbon electrode (GCE). Emodin, an active ingredient of traditional Chinese medicines was used as template.…”
Section: Mims-based Bio-mimetic Sensorsmentioning
confidence: 99%
“…The novel sensor was tested for the determination of emodin content in Sanhuang tablets and compared with classical HPLC measurements. Results of these methods were about 2.49 × 10 −1 (mg·tablet −1 ) and 2.46 × 10 −1 (mg·tablet −1 ), respectively [ 296 ].…”
Section: Mims-based Bio-mimetic Sensorsmentioning
confidence: 99%
“…In the meanwhile, the preparation of most of the adsorbent materials and the extraction processes are time-consuming, unfriendly to environment, high-cost, and low-efficiency. [16] It is well-known that the typical extraction procedure of the active components of TCMs at current stage is as follows. The herbs containing rutin or rhoifolin are cut into pieces and dipped in large volume of water and/or ethanol.…”
Section: Introductionmentioning
confidence: 99%